2020
DOI: 10.1007/s10980-020-01013-9
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting land use legacy effects on forest landscape dynamics in the Italian Alps and the Apennines

Abstract: Context: Land use legacies of human activities and recent post-abandonment forest expansion have extensively modified numerous forest landscapes throughout the European mountain ranges. Drivers of forest expansion and the effects of changes on ecosystem services are currently debated.Objectives: i) to compare landscape transition patterns of the Alps and the Apennines (Italy), ii) to quantify the dominant landscape transitions, and iii) to measure the influence of climatic, topographic and anthropogenic drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 90 publications
3
27
1
Order By: Relevance
“…The abrupt reduction of traditional agro‐pastoral practices at the highest elevations observed in Europe in the last decades has promoted shrubs and tree encroachment in the Alps and Pyrenees (Gehrig‐Fasel et al, 2007; Holtmeier & Broll, 2007; Ameztegui et al, 2016). After recent abandonment, forest expansion was observed throughout the Apennines although woody‐plant encroachment was observed to be progressively less intense at higher elevations (Malandra et al, 2019; Garbarino et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abrupt reduction of traditional agro‐pastoral practices at the highest elevations observed in Europe in the last decades has promoted shrubs and tree encroachment in the Alps and Pyrenees (Gehrig‐Fasel et al, 2007; Holtmeier & Broll, 2007; Ameztegui et al, 2016). After recent abandonment, forest expansion was observed throughout the Apennines although woody‐plant encroachment was observed to be progressively less intense at higher elevations (Malandra et al, 2019; Garbarino et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The odds ratio (e β 1 ) for percentage shrub cover was estimated as 1.07, which means that an increase of 1% in the canopy cover of shrubs enhanced the chances of -Fasel et al, 2007;Holtmeier & Broll, 2007;Ameztegui et al, 2016). After recent abandonment, forest expansion was observed throughout the Apennines although woodyplant encroachment was observed to be progressively less intense at higher elevations (Malandra et al, 2019;Garbarino et al, 2020).…”
Section: Relationship Between Fagus Sylvatica Recruitment and Shrubsmentioning
confidence: 99%
“…Cultural landscapes include woodlands [55], forests, water systems, vineyards, national parks [74], and archaeological and mixed sites. Additionally, considering the multi-and inter-disciplinary nature of the theme of cultural landscapes, cultural [75] and ecosystem services [76], biodiversity [23,77], vegetation and land cover [63,78], and land-use changes [79,80] should be embedded into the documentation of cultural landscapes to capture the "whole story." Along with its intangible values, it is essential to further investigate traditional ecological knowledge [81,82], traditional agricultural knowledge [83], and local fire ecology [84,85].…”
Section: Technical Barriersmentioning
confidence: 99%
“…During the last decades, changes in the vegetation cover have been recorded in many mountain ecosystems. Past studies revealed changes in dominant plant species at a global scale [16], while locally they show an increase in the extent of tree and shrub coverage (since 1960, forest cover in the Italian Alps doubled its extension [17]; for differences between the Alps and Apennines see [18]; for the French Alps [19]; for the Swiss Alps [20]) and a general upwards altitudinal shift of the treeline ecotone (for the Swiss Alps [21,22]; for the southwestern French Alps [23]; for the Scandinavian Mountains [24]; for a global survey [25]), but site topography and small-scale factors might outweigh the effects of global warming ( [26]; see the "conservative" pattern of the Central European Alps [27] and references therein). On the other hand, climate change is not the only disturbing factor; therefore, assessing a direct role of global warming on these modifications is difficult in the Alps and on the hilly slopes of southern Piedmont (Italy), where landscapes have been modelled by millennia of human pressure, recently followed by changes in land use as agricultural and pastoral intensification or abandonment, or land abandonment (for the European Alps see [28,29]; for the Italian Alps [30] and Piedmont [31,32]).…”
Section: Introductionmentioning
confidence: 99%